PENGARUH LIKUIDITAS, LEVERAGE, DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK - Winata, Feby Rahmat Adi; Retnaningdiah, Dian (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
Objective: This study aims to determine the effect of liquidity, leverage, and capital structure on dividend policy in transportation and logistics companies listed on the IDX. Research Method: The researcher used a quantitative research method. This study uses causal associative research, which is a method that aims to analyze the cause and effect relationship between variables. The population in this study consisted of 37 transportation and logistics companies listed on the Indonesia Stock Exchange. The sample used was 6 companies selected using the Purposive Sampling sampling technique. This study uses secondary data obtained from the annual financial reports of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Results: The results of this study indicate that liquidity has a significant effect on dividend policy, while leverage and capital structure do not have a significant effect on dividend policy.